2016
DOI: 10.1590/1981-22562016019.160031
|View full text |Cite
|
Sign up to set email alerts
|

Oral health conditions and activities of daily living in an elderly population in Brazil

Abstract: Objective: To analyze the relationship between the oral health status and functional capacity in performing basic activities of daily living of a population of elderly persons. Method: A cross-sectional population-based study with 441 individuals aged 60 years or over both genders was performed in the municipality of Macaíba, Rio Grande do Norte. From intraoral epidemiological examination, the degree of caries attacks (CPO-D index), periodontal condition (CPI and PIP indexes), the use and need for dental prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
0
5
0
12
Order By: Relevance
“…Women pay more attention to their appearance, while men do not heed it. In addition women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and quicker and more flexible response than women [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Women pay more attention to their appearance, while men do not heed it. In addition women are more sensitive to emotion and empathy while men are more likely to care about better physical environment and quicker and more flexible response than women [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Brasil 9 ; *Considerada a totalidade de indivíduos que necessitaram e ou passaram pela situação em questão para realizar cálculo de porcentagem. Dificuldade Funcional: DF; Atividades Básicas de Vida Diária: ABVD; Atividades Intrumentais de Vida Diária: AIVD; Número: N. Uso de prótese dentária Não 2740 (12) 98 (15) 173 (17) 3011 (13) Próteses dentárias totais em uma das arcadas ou para substituir determinado número de dentes 3983 (18) 52 (8) 79 (8) 4115 (17) Próteses dentárias totais para ambas as arcadas 3404 (15) 68 (10) 132 13…”
Section: Resultadounclassified
“…A saúde bucal é um importante parâmetro a ser considerado, devido à sua significativa contribuição para a formação da variável percepção de saúde 1 . Apresenta, ainda, a saúde bucal, concomitante influência nas condições funcionais de idosos e na sua qualidade de vida 2,13 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Corroborating previous studies, the findings showed that female individuals aged 60 years or older had more frequent medical appointments (OR = 1.35) (6,19) when compared to males. It is known that men usually seek care late, usually when the disease is already installed (20) , reducing the number of years they live (21) . On the other hand, women commonly use lifelong health services more often for reasons related to their own gender, and perceive conditions with potential health risk earlier.…”
Section: Discussionmentioning
confidence: 99%